MAF Amplification and Adjuvant Clodronate Outcomes in Early-Stage Breast Cancer in NSABP B-34 and Potential Impact on Clinical Practice. Issue 4 (28th May 2021) - Paterson, Alexander H G; Lucas, Peter C; Anderson, Stewart J; Mamounas, Eleftherios P; Brufsky, Adam; Baez-Diaz, Luis; King, Karen M; Lad, Thomas; Robidoux, André; Finnigan, Melanie; Sampayo, Miguel; Tercero, Juan Carlos; et al.
Abstract: Background: The Adjuvant Zoledronic Acid (ZA) study in early breast cancer (AZURE) showed correlation between a nonamplified MAF gene in the primary tumor and benefit from adjuvant ZA. Adverse ZA outcomes occurred in MAF-amplified patients. NSABP B-34 is a validation study. Methods: A retrospective analysis of MAF gene status in NSABP B-34 was performed. Eligible patients were randomly assigned to standard adjuvant systemic treatment plus 3 years oral clodronate (1600 mg/daily) or placebo. Tumors were tested for MAF gene amplification and analyzed for their relationship to clodronate for disease-free survival (DFS) and overall survival (OS) in MAF nonamplified patients. All statistical tests were 2-sided . Results: MAF status was assessed in 2533 available primary tumor samples from 3311 patients. Of these, 37 withdrew consent; in 77 samples, no tumor was found; 536 assays did not meet quality standards, leaving 1883 (77.8%) evaluable for MAF assay by fluorescence in situ hybridization (947 from placebo and 936 from clodronate arms). At 5 years, in MAF nonamplified patients receiving clodronate, DFS improved by 30% (hazard ratio = 0.70, 95% confidence interval = 0.51 to 0.94; P  =   .02). OS improved at 5 years (hazard ratio = 0.59, 95% confidence interval = 0.37 to 0.93; P  =   .02) remaining statistically significant for clodronate throughout study follow-up. Conversely, adjuvant clodronate in women with MAF -amplified tumors was not associated with benefit but rather possible harm in some subgroups. Association between MAF status and menopausal status was not seen. Conclusions: Nonamplified MAF showed statistically significant benefits (DFS and OS) with oral clodronate, supporting validation of the AZURE study.